Study on Laser Welding of Transparent Thermoplastic Resin Plates - YAMAKAWA, Masafumi; NAKAMURA, Takashi; HASEGAWA, Tatsuya; HAYAKAWA, Shinya (Nihon Kikai Gakkai ronbunshū. C, 2008)
Characteristics of a new laser welding method for transparent thermoplastic resin plates are studied. The absorptivity on the surface is enhanced by pretreatment of sandblasting. It is found that the absorptivity due to roughness increases up to 36% for Polycarbonate and 21% for PMMA by sandblasting of #220. During welding process, the welded portion becomes transparent and the absorptivity due to roughness decreases down to 12% for Polycarbonate and 0% for PMMA. The shearing strength increases with the laser fluence, but it abruptly decreases by the formation of bubbles. The shearing strength also increases with the retaining pressure up to 0.15 MPa and it becomes nearly constant.